Classification of retinal diseases from OCT images using deep learning models - Mokarrom, Md Saif; Shuvo, Md Anonto; Oyon, Nazmul Hasan; Munaja, Rifha Hossain; Roy, Soumik (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.